2020
DOI: 10.1093/mnras/staa1884
|View full text |Cite
|
Sign up to set email alerts
|

Near mean motion resonance of terrestrial planet pair induced by giant planet: application to Kepler-68 system

Abstract: Abstract In this work, we investigate configuration formation of two inner terrestrial planets near mean motion resonance (MMRs) induced by the perturbation of a distant gas-giant for the Kepler-68 system, by conducting thousands of numerical simulations. The results show that the formation of terrestrial planets is relevant to the speed of Type I migration, the mass of planets, and the existence of giant planet. The mass and eccentricity of the giant planet may … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…We adopt a reasonable reduction factor f1 = 0.3 in Eqn. 4 (Pan et al 2020), where the gas accretion of planets is not considered.…”
Section: Inward Migration Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopt a reasonable reduction factor f1 = 0.3 in Eqn. 4 (Pan et al 2020), where the gas accretion of planets is not considered.…”
Section: Inward Migration Formationmentioning
confidence: 99%
“…Furthermore, inside-out planetary formation model indicates that planets in the inner disk are produced sequentially at the pressure maximum by pebble collision or near snow line by streaming instabilities, thereby revealing formation of tightly-packed planetary system (Chatterjee & Tan 2014;Ormel et al 2017). Besides, tidal circularization, secular resonance sweeping, planetary interaction as well as stellar magnetosphere may also rebuild planetary configurations to yield compact and close-in systems (Nagasawa & Ida 2011;Pan et al 2020;Liu & Ji 2020).…”
Section: Introductionmentioning
confidence: 99%
“…4.1 we already have shown that there are different ways to establish the separation between planets c and d, although the small distant migration torque favours a scenario with high 𝐴 e . In addition, the radial gravity from the exterior disc on the planets in the cavity (Nagasawa et al 2003;Pan et al 2020) might play an important role in 3BRs trapping and escape, which has not been investigated in this study. A setup alternative to dCav_gImp_cOL would be for planet d and e to become trapped in 4:3 MMR, instead of 3:2, after planet formation and to let three planets fall in the cavity during Stage II, such that the cavity radius coincides with the current location of planet e. This would at first glance be more natural as the 3BR Φ 2,5,3 b,c,d and Φ 2,6,4 c,d,e which form during Stage I remain librating.…”
Section: Discussionmentioning
confidence: 93%
“…From the statistic results, we find that there are plenty of planet pairs in the configuration of near MMRs especially the first order resonances, such as 2:1 and 3:2 MMRs (Lissauer et al 2011;Wang et al 2012;Lee et al 2013;Wang & Ji 2014, 2017Antoniadou & Libert 2020). However, the peaks in the distribution of period ratios are shown not in the exact location of MMRs, but a little departure from them (Wang et al 2012;Lee et al 2013;Steffen et al 2013;Wu et al 2019;Pan et al 2020). Most of the planet pairs pipe up at the location larger than the exact MMRs.…”
Section: Introductionmentioning
confidence: 88%
“…If planets migrate to the inner region of the system, the effect of the tidal raised by the star can destroy the configuration of MMRs and become near MMRs configuration. Based on this formation scenario, we investigated the configuration formation of KOI-152 system with planets in near 4:2:1 MMRs (Wang et al 2012), the formation of near 2:1 and 3:2 MMRs effected by the properties of star, the speed of type I migration (Wang & Ji 2014), the effect caused by the mass accretion process and the possible outward migration , and the existence of giant planets in planetary systems (Sun et al 2017;Pan et al 2020).…”
Section: Introductionmentioning
confidence: 99%